Eksekusi Aset Debitor yang Berada Di Luar Negeri dalam Penyelesaian Sengketa Kepailitan - Rizka Rahmawati (Faculty of Law, Universitas Pattimura, 2019)
In order to carry out business activities, it is not uncommon for someone to make a debt to have enough capital. These accounts payable activities of course require objects that are a guarantee to give a sense of security to creditors. In its development it is not uncommon for collateral objects to be held by debtors abroad. However, if the collateral object is located abroad, it will not be easy to execute as a debt repayment tool because of the state sovereignty that must be respected and the territoriality principle adopted by a country. The problem in this writing is about how Indonesia's national legal regulation regarding debtors 'assets is located abroad and how efforts can be made so that debtors' assets residing abroad can be executed as debt repayment tools. This research will be conducted using a type of normative juridical research with a type of legislative approach (concept approach) and a conceptual approach. According to the provisions of Article 212 PKPU UUK, that property owned by bankrupt debtors abroad can be used as bankrupt boedel. The provisions of the article give the right to a creditor to obtain repayment by using debtor's assets which are not bound to him which are outside the jurisdiction of the Unitary State of the Republic of Indonesia. In order for collateral objects to be used abroad to be used as a debt repayment tool, a number of ways can be taken, namely by a general court process, bilateral agreements (diplomatic agreements), diplomatic channels, or using the UNCITRAL Law on Cross Model. Border Insolvency with Guide to Enactment.